2022
DOI: 10.1002/anie.202201148
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining Electron Transfer Pathways Extends Biohybrid Photoelectrode Stability to Years

Abstract: The exploitation of natural photosynthetic enzymes in semi-artificial devices constitutes an attractive and potentially sustainable route for the conversion of solar energy into electricity and solar fuels. However, the stability of photosynthetic proteins after incorporation in a biohybrid architecture typically limits the operational lifetime of biophotoelectrodes to a few hours. Here, we demonstrate ways to greatly enhance the stability of a mesoporous electrode coated with the RC-LH1 photoprotein from Rhod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Investigations in situ and in operandum are crucial for the rational design of high-performing biohybrids, particularly in the context of recent and more complex benchmark architectures that drive large photocurrent densities but encounter multiple loss channels from short circuits, electron transfer bottlenecks, and excitation quenching. 4,[22][23][24][25] In this work, we utilized a combined spectroelectrochemical instrument, based on a ms/ms pump-probe Joliot-type spectrophotometer, to measure the redox states of Rba sphaeroides RC-LH1 complexes adsorbed on a semi-transparent mesoporous indium tin oxide electrode (mITO -Figure 1D). By simultaneously recording photocurrents and spectrally derived functional bRC oxidation states, kinetic bottlenecks and loss processes were identified at various stages of excitation and electron transfer in this mITO|cyt c|RC-LH1 electrode.…”
Section: Context and Scalementioning
confidence: 99%
See 2 more Smart Citations
“…Investigations in situ and in operandum are crucial for the rational design of high-performing biohybrids, particularly in the context of recent and more complex benchmark architectures that drive large photocurrent densities but encounter multiple loss channels from short circuits, electron transfer bottlenecks, and excitation quenching. 4,[22][23][24][25] In this work, we utilized a combined spectroelectrochemical instrument, based on a ms/ms pump-probe Joliot-type spectrophotometer, to measure the redox states of Rba sphaeroides RC-LH1 complexes adsorbed on a semi-transparent mesoporous indium tin oxide electrode (mITO -Figure 1D). By simultaneously recording photocurrents and spectrally derived functional bRC oxidation states, kinetic bottlenecks and loss processes were identified at various stages of excitation and electron transfer in this mITO|cyt c|RC-LH1 electrode.…”
Section: Context and Scalementioning
confidence: 99%
“…An applied potential of +160 mV vs. SHE was used to optimally drive a photocathodic current, as described previously for cyt c mediated bRC photocathodes. 4,26 Excitation was provided either by an LED peaking at 590 nm, or by 5 ns laser flashes at 532 nm (Figures 2A and 2B). Photooxidation of the bRC primary electron donor was monitored at 865 nm (e 865 = 112 G 6 mM À1 cm À1 , see Straley et al 27 ), with simultaneous recording of photoinduced electron transfer at the electrode interface using chronoamperometry.…”
Section: Constructing the Spectroelectrochemical Apparatusmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, to support a photocurrent over multiple RC turnovers, cyt c molecules have to remain largely confined to the plane of the electrode surface during fabrication and operation. That this occurs is supported by studies that have shown that the photocurrents remain stable for hours after free cyt c is removed from the electrolyte. Third, the orientation of the RC on the electrode may occlude cyt c access, restricting the rate of P870 + reduction . These differences result in RC electron transfer turnover frequencies (TOF) that are typically on the order of 10 to 150 e – s –1 . , These are only a fraction of the maximal RC TOF of up to 2300 e – s –1 that can be observed with purified proteins in solution. , …”
Section: Introductionmentioning
confidence: 99%
“…That this occurs is supported by studies that have shown that the photocurrents remain stable for hours after free cyt c is removed from the electrolyte. 23 25 Third, the orientation of the RC on the electrode may occlude cyt c access, restricting the rate of P870 + reduction. 26 These differences result in RC electron transfer turnover frequencies (TOF) that are typically on the order of 10 to 150 e – s –1 .…”
Section: Introductionmentioning
confidence: 99%